2010
DOI: 10.1007/s10570-010-9419-5
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-mechanical properties of microfibrillated cellulose-reinforced partially crystallized PLA composites

Abstract: Polylactic acid (PLA) in a crystallized state has mechanical properties at high temperatures superior to PLA in an amorphous state. However, a long annealing time is required to fully crystallize PLA. In this study, microfibrillated cellulose (MFC)-reinforced partially crystallized PLA composites were produced, with the goal of reducing the time required to fabricate PLA parts. A series of PLA/MFC composites at a fiber content of 10 wt% from degree of crystallinity (Xc) 0 to 43% was obtained by annealing at 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
67
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(80 citation statements)
references
References 18 publications
11
67
0
2
Order By: Relevance
“…This effect on the crystallinity of polymer materials is reported in various other studies, in which polymers have been used, like PLA [2] , PCL [21] , PVA [22] and PHBV [23] . These results suggest that the effect produced by the cellulose on the crystallinity of polymer materials is independent of the type of polymer matrix used, and is therefore mainly related to the nature of this filler.…”
Section: Santos F A; Tavares M I B -Development and Characterisupporting
confidence: 67%
See 1 more Smart Citation
“…This effect on the crystallinity of polymer materials is reported in various other studies, in which polymers have been used, like PLA [2] , PCL [21] , PVA [22] and PHBV [23] . These results suggest that the effect produced by the cellulose on the crystallinity of polymer materials is independent of the type of polymer matrix used, and is therefore mainly related to the nature of this filler.…”
Section: Santos F A; Tavares M I B -Development and Characterisupporting
confidence: 67%
“…Renewable materials from natural sources have been extensively researched to replace traditional polymers used in various applications [1,2] . These materials have advantages such as biodegradability, biocompatibility, low toxicity and low cost [3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic mechanical analysis (DMA) revealed that PHBV chain mobility was restrained in the vicinity of the CNCs. Suryanegara et al 87 developed a kneading technique to disperse MFCs to 10 wt% loadings in PLA. They investigated the deformation behaviour of the composites as a function of PLA crystallinity.…”
Section: At Low To Medium Cellulose Loadings Percolated Network Formmentioning
confidence: 99%
“…It has subsequently been established that MFC can be readily prepared using a range of mechanical treatments including grinding, microfluidising, sonication and homogenization [1,[3][4][5][6][7][8][9]. Interest in the use of MFC to reinforce a polymer composite has grown over the last decade due to the fibres' high aspect ratio, crystallinity, stiffness and specific surface area [3,10].…”
Section: Introductionmentioning
confidence: 99%